Establishment of linkage phase, using Oxford Nanopore Technologies, for preimplantation genetic testing of Coffin-Lowry syndrome with a de novo RPS6KA3 mutation - Wen, Xiaojun; Du, Jing; Li, Zhiming; Liu, Nengqing; Huo, Junye; Li, Jieliang; Ke, Wanna; Wu, Jiaqi; Fang, Xiaowu; Lin, Xiufeng (Frontiers in Genetics, 2023)
Background: This study aimed to perform preimplantation genetic testing (PGT) for a female Coffin-Lowry Syndrome (CLS) patient with a de novo mutation (DNM) in RPS6KA3. It was challenging to establish the haplotype in this family because of the lack of information from affected family members. Hence, we explored a new and reliable strategy for the detection of the DNM in PGT, using Oxford Nanopore Technologies (ONT) and the MARSALA platform.We performed whole-exome sequencing (WES) on the proband and confirmed the pathogenic mutation by Sanger sequencing. The proband then underwent PGT to prevent the transmission of the pathogenic mutation to her offspring. We diverged from the conventional methods and used long-read sequencing (LRS) on the ONT platform to directly detect the mutation and nearby SNPs, for construction of the haplotype in the preclinical phase of PGT. In the clinical phase of embryo diagnosis, the MARSALA method was used to detect both the SNP-based haplotype and chromosome copy number variations (CNVs), in each blastocyst. Finally, a normal embryo was selected by comparison to the haplotype of the proband and transferred into the uterus. Sanger sequencing and karyotyping were performed by amniocentesis, at 17 weeks of gestation, to confirm the accuracy of PGT.Using WES, we found the novel, heterozygous, pathogenic c.1496delG (p.Gly499Valfs*25) mutation of RPS6KA3 in the proband. The SNP-based haplotype that was linked to the pathogenic mutation site was successfully established in the proband, without the need for other family members to be tested with ONT. Eight blastocysts were biopsied to perform PGT and were assessed with a haplotype linkage analysis (30 SNP sites selected), to give results that were consistent with direct mutation detection using Sanger sequencing. The results of PGT showed that three of the eight blastocysts were normal, without the DNM. Moreover, the patient had a successful pregnancy, after transfer of a normal blastocyst into the uterus, and delivered a healthy baby.The ONT platform, combined with the MARSALA method, can be used to perform PGT for DNM patients without the need for other samples as a reference.